PEMANFAATAN LIMBAH KULIT BIJI NYAMPLUNG UNTUK BAHAN BAKAR BRIKET BIOARANG SEBAGAI SUMBER ENERGI ALTERNATIF - Arif Budiarto; Ganish Eko Mayndra; Didi Dwi Anggoro (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
This research was started by pirolized the  main  matter, nyamplung’s seed peel into char with three kinds of adhesive agent as is sodium silicate, wheat powder, and tapioca starch. The aims of this research are to know the right kind of the adhesive, to know the optimal particle size of the nyamlung seed’s peel ash, to know the optimal of  the adhesive concentration, and to know the optimal condition of the briquette making by using response surface methodology (RSM). This research uses two steps, first is first is certaining the right kind of the adhesive agent and second one is optimization of independent variables as are the concentration of adhesive agent and the char particle size. The result of this research shows that the best kind of adhesive agent which is used to produce a good briquette is tapioca starch. Briquette with 17,66% adhesive agent and 20 mesh particle size results  the highest heating value as is 6772,582 kal/gr  which has fulfilled the  standart of Indonesian and Japanese. Briquette with 6,34 % adhesive agent and 20 mesh particle size results  the worst stabilty and the highest % loss as is 33,56 % while briquette with 16 % adhesive agent and 40 mesh particle size also 17,66 % adhesive agent and 20 mesh particle size results the best stability and the lowest % loss consecutively as is 0,83 % and 1,24 %. Stability test shows that briquette product is stable in diameter and height all the time. From this research’s results, it is wished to take a further research that study about the other independent variables to produce the better nyamplung’s seed peel briquette so it can give a contribution for inventing alternative enviromental agreeable fuel.